PGC-1? integrates insulin signaling with mitochondrial physiology and behavior in a Drosophila model of Fragile X Syndrome. - Weisz, E.D.; Fenton, A.R.; Jongens, T.A. (NPJ metabolic health and disease, 2024)
Fragile X Syndrome (FXS) is the most prevalent monogenetic form of intellectual disability and autism. Recently, dysregulation of insulin signaling (IS) and aberrations in mitochondrial function have emerged as robust, evolutionarily conserved components of FXS pathophysiology. However, the mechanisms by which altered IS and mitochondrial dysfunction impact behavior in the context of FXS remain elusive. Here, we show that normalization of IS improves mitochondrial volume and function in flies that lack expression of dfmr1, the Drosophila homolog of the causal gene of FXS in humans. Further, we demonstrate that dysregulation of IS underlies diminished expression of the mitochondrial master regulator PGC-1?/Spargel in dfmr1 mutant flies. These results are behaviorally relevant, as we show that pan-neuronal augmentation of PGC-1?/Spargel improves circadian behavior in dfmr1 mutants. Notably, we also show that modulation of PGC-1?/Spargel expression in wild-type flies phenocopies the dfmr1 mutant circadian defect. Taken together, the results presented herein provide a mechanistic link between mitochondrial function and circadian behavior both in FXS pathogenesis as well as more broadly at the interface between metabolism and behavioral output.